DETERMINAN TERJADINYA KECENDERUNGAN KECURANGAN AKUNTANSI (FRAUD) PADA DINAS PEMERINTAH SE KABUPATEN GROBOGAN (Accounting Analysis Journal, 2015)
Penelitian ini bertujuan untuk menggali persepsi para pegawai di instansi pemerintahan mengenai faktor- faktor yang mempengaruhi kecenderungan kecurangan akuntansi (fraud) seperti keefektifan pengendalian internal, budaya etis, kesesuaian kompensasi, penegakan peraturan, asimetri informasi, dan komitmen organisasi. Penelitian ini menggunakan sampel sejumlah 182 pegawai instansi dinas pemerintahan di Kabupaten Grobogan. Teknik pengambilan sampel menggunakan convenience sampling. Analisis data dalam penelitian ini menggunakan analisis full model Structural Equation Modeling (SEM) dengan alat analisis smartPLS 2.0. Hasil penelitian menunjukkan terdapat pengaruh negatif keefektifan pengendalian internal, kesesuaian kompensasi, dan penegakan peraturan terhadap kecenderungan kecurangan akuntansi di sektor pemerintahan, terdapat pengaruh positif asimetri informasi terhadap kecenderungan kecurangan akuntansi di sektor pemerintahan, tidak terdapat pengaruh negatif budaya etis dan komitmen organisasi terhadap kecenderungan kecurangan akuntansi di sektor pemerintahan. Saran pada penelitian selanjutnya diharapkan untuk melakukan observasi atas objek penelitian untuk mengetahui kesediaan objek penelitian, dan menambah faktor lain yang mempengaruhi kecenderungan kecurangan akuntansi.This research aims to explore the perceptions of employees in government agencies about the factors that affect to the of accounting fraud as internal control effectiveness, ethical culture, compensation, compliance enforcement of regulations, information asymmetry, and organizational commitment. This research using 182 employees as the samples by the respondent government agencies working in financial at the Department of Grobogan Regency. This research using convenience sampling. Data analysis in this research using a model full analysis structural equation modelling (SEM) with a smartPLS2.0. The results of the research showed that there are negative influences between the effectiveness of the control, the suitability of compensation , and the enforcement of the regulations by the tendency of accounting fraud in the government sector. there is a negative influence of with the tendency of accounting fraud in the government sector, there is a positive influence of asymmetry of information with accounting fraud trends in the government sector, there is no negative influence of ethical culture and organizational commitment with a tendency of accounting fraud in the sector of government. The advice in this research to conduct observation over the object of research to determine the willingness of the research object, and add to other factors that affect the tendency of accounting fraud.